Cost–benefit analysis of the intraoperative parathyroid hormone assay in primary hyperparathyroidism. Issue 2 (24th August 2016) - Badii, Benedetta; Staderini, Fabio; Foppa, Caterina; Tofani, Lorenzo; Skalamera, Ileana; Fiorenza, Giulia; Qirici, Eva; Cianchi, Fabio; Perigli, Giuliano
Abstract: Background: The purpose of this study was to evaluate the usefulness of the routine intraoperative intact parathyroid hormone (IOPTH) assay, the role of unilateral and bilateral cervical exploration and of preoperative imaging, and to do a cost–benefit analysis in parathyroidectomy for primary hyperparathyroidism. Methods: Two hundred sixty‐four patients who underwent operations between January 2000 and March 2015 were retrospectively divided into 2 groups. Results: Group A (IOPTH) was composed of 64 patients. Ultrasonography and technetium‐99m‐sestamibi (MIBI) identified the adenoma in 38 cases. Bilateral exploration was performed in 43 patients; of which 2 failures occurred. The IOPTH false‐negative rate was 18.4%. The average cost was €1297.30. Group B (without IOPTH) was composed of 200 patients. Ultrasonography and MIBI identified the adenoma in 113 cases. Bilateral exploration was performed in 129 patients; of which 2 failures occurred. The average cost was €618.75. Conclusion: The IOPTH assay should be used only in few selected cases because of its high cost. The experience of the team is essential to obtain a high cure rate. © 2016 Wiley Periodicals, Inc. Head Neck 39: 241–246, 2017